The assessment on the acceptance of waste materials as a partial cement replacement in Malaysian construction industry - Zaidatul Syahida, Adnan; Nur Farhayu, Ariffin; Sharifah Maszura, Syed Mohsin; Nor Hasanah, Abdul Shukor Lim (IOP Publishing Ltd, 2021)
The numbers of Malaysia construction industry had been increasing in several years with the large construction building and infrastructures projects had been constructed. Therefore, these developments led to an increase of cement production. The production of cement causes a wider environmental implication such as air pollution, water pollution and soil pollution which are very dangerous for human health. This is due to the manufacturing of cement that release dust, toxic and carbon dioxide emissions, which is a significant contributor of greenhouse gases. To overcome this problem, several researches had been conducted for the past few decades to develop a new material to replace cement. Most of the materials selected are from waste materials that has similar chemical properties and mechanical properties. From the research, most of the results show a positive performance in concrete and suitable to be use as a cement replacement. Unfortunately, the research stops at the research stage where it is rarely seen that these waste materials had been used in construction, especially in Malaysia. Most of the developers did not corporate these waste materials as a cement replacement in their construction work due to unclear reasons. Therefore, this study had been conducted to investigate the factors of un-implementation of waste materials in construction industry especially in Malaysian construction. This can be achieved by intensive literature review on properties and performance of waste materials in concrete. An interview session with an expertise also had been conducted to design a questionnaire that later had been distributed to 140 respondents from construction site background especially registered contractor Class G1-G7 all around Peninsular Malaysia. The data had been analyzed and the factor contribute to un-implemented of waste materials in construction had been identified. From the data analysis, factors that contributes to the un-implemented are due to lack of awareness and knowledge about waste materials as a cement replacement. Thus, to overcome this problem, respondents suggest that the workshop need to be conducted to spread the awareness and give a knowledge regarding waste materials as a cement replacement.